Rural-urban migration, urban unemployment, and rural income disparities in the Philippines - Gonzalez, Eduardo T. (1990)
In the Harris-Todaro model, a demand-augmenting policy, to the extent that it raises job probabilities, and hence, the positive urban-rural income differential, has the effect of stimulating a higher migration flow from the countryside, even in the face of massive urban unemployment. This paper attempts to verify empirically the validity of the model in explaining Philippine rural-urban migration. The results indicate a strong monotonic relationship between urban-rural income differential and migration propensity, suggesting that urban unemployment expansion remainsa valid policy, it is apparent that output can be increased only if the supply of labor to urban areas is slowed down and reabsorbed in alternative employment in agriculture.
Keywords: Rural-urban migration; Income -- Regional disparities; Unemployment -- Regional disparities